Joint planning for spare parts inventory and preventive maintenance in a multi-echelon network. (2016) - Shi, Yue; Xiang, Yisha; Jin, Tongdan; Li, Yueqing
Spare parts inventory and preventative maintenance play a vital role in ensuring operational availability of capital equipment. This paper investigates the cost-reliability benefits from jointly optimising preventive maintenance and spare parts inventory. Due to the problem complexity and the mathematical intractability, we propose a simulation framework to tackle this joint planning problem in a multi-echelon network. The general simulation model developed in this paper allows a closer-to-reality analysis of joint decisions on spare parts inventory and preventive maintenance for a fleet of equipment with increasing failure rates. Both block- and age-based preventive maintenance policies are considered. We also adopt a performance-based contracting approach to analysing the trade-off between inventory cost and target availability in different incentive mechanisms. Numerical experiments are presented to illustrate the effectiveness of the joint policies.